Node Localization in a Network of Doppler Shift Sensor Using Multilateral Technique - Akhigbe-mudu Thursday Ehis (Tecno Scientifica Publishing, 2022)
Localization is the process of determining the location of a target(s) in a given set of coordinates using a location system.However, due to environmental uncertainty and Doppler effects, mistakes in distance estimations are created in physical situations, resulting in erroneous target location. A range-based multilateration technique is presented to improve localization accuracy. Multilateration is the method of calculating a position based on the range measurements of three or more anchors, with each satellite acting as the sphere's center. The distance between the satellite and the receiver is represented by the sphere's radius. The intersection of four spherical surfaces determines the receiver's position. This study's approach proposes a simple measure for evaluating GRT based on reference node selection. The algorithm utilizes these reference nodes, seeking to determine the optimal location based on ranging error. It calculates GRT values for each of the three node combinations. This study evaluates the performance of range-based localization using the Multilateration Algorithm with a Correcting Factor. The correction factor is applied to both the anchor node and the node to be measured; hence, the localization error is significantly reduced. In terms of how much time and money it takes to run and how much hardware it costs, the new method is better than some of the current methods.